Microspalax atlanticus sp. nov. (Acariformes: Alloptidae), the first feather mite from a procellariiform bird in Brazil (Aves: Procellariiformes) - Hernandes, Fabio Akashi [UNESP] (Systematic & Applied Acarology Soc London, Natural History Museum, 2019)
A new feather mite species of the genus Microspalax Megnin & Trouessart, 1884 (Alloptidae: Microspalacinae) is described from the Atlantic petrel, Pterodroma incerta (Schlegel, 1863), in Brazil. Males of M. atlanticus sp. nov. differ from M. pterodromae Dubinin, 1949 mostly by the wider opisthogastric shields and setae ps3 inserted at posterior third of that shield. This is the first representative of the genus described from Brazil, and the first feather mite described from a procellariiform bird in the country. A key to males of Microspalax species is presented.
Keywords: Acariformes; Astigmata; systematics; Neotropics; endangered bird